THE IMPLEMENTATION OF INTEGRATED-APPROACH ON GERD (I-AGE) PROJECT IN FISHERMEN AS A MODEL OF INTERRELATION OF RESEARCH-BASED HEALTHCARE AND TEACHING - Ahmad Fariz Malvi Zamzam Zein (Proceedings of the International Conference on Applied Science and Health, 2019)
-